2019
DOI: 10.3390/en12030533
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Optimization for Integration of Renewable Energy Technologies in District Energy Systems for Cost-Effective Use

Abstract: Stochastic optimization of a district energy system (DES) is investigated with renewable energy systems integration and uncertainty analysis to meet all three major types of energy consumption: electricity, heating, and cooling. A district of buildings on the campus of the University of Utah is used as a case study for the analysis. The proposed DES incorporates solar photovoltaics (PV) and wind turbines for power generation along with using the existing electrical grid. A combined heat and power (CHP) system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
7
0
2
Order By: Relevance
“…A simple payback period (SPB) is the number of years necessary to recover the project cost of investment under consideration and can be worked out by using Equation (10).…”
Section: Financial Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple payback period (SPB) is the number of years necessary to recover the project cost of investment under consideration and can be worked out by using Equation (10).…”
Section: Financial Modelmentioning
confidence: 99%
“…Karasmanaki and Tsantopoulos [9] researched the attitude of RES students in the Department of Forestry and Management of the Environmental and Natural Resources at the Democritus University of Thrace in Greece since they are possible experts in RES, and the results show that students support renewables and have awareness about current polluting energy systems. Tran and Smith [10] developed an analysis on renewable energy systems integration and uncertainty to meet the three major types of energy consumption: Electricity (solar photovoltaic and wind), heating (combined heat and power) and cooling (electricity) at facilities on the campus of the University of Utah. They found that the uncertainty of energy loads and power generation from renewable energy heavily affects the operating cost of the district energy system.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on the technology of RIES has been considerable. Most of these studies concentrate on specific technologies like the optimization of multi-energy storage [12,18], heat pumps with a solar assisted ground source [19,22,23], low temperature district heating networks [24,25], integration of renewable energy [26], and so on. The global spread of this kind of energy use is also considerable.…”
Section: Regional Integrated Energy System In City Planningmentioning
confidence: 99%
“…Tran and Smith [7] propose a stochastic approach to minimize the operating cost of a district energy system (DES), including a CHP system, natural gas boilers, solar photovoltaics (PV), and wind turbines for generation of power, heating, and cooling. A district of buildings on a university campus is used as a case study.…”
Section: Optimization Of Design and Operation Of Groups Of Energy Conmentioning
confidence: 99%